Penilaian Sesbania sesban sebagai Spesies yang Diduga Invasif di Daerah Perkotaan Sangatta, Kalimantan Timur - Titis Hutama Syah; Arbain Arbain (Institut Pertanian Bogor, 2019)
Sangatta as the capital of East Kutai Regency is a rapidly growing urban area. The rapid growth and development of Sangatta resulted in the increase of open space. For this reason, the government and local communities tried to reforest the residential areas by planting many plant species. However, generally the chosen species were not the local ones and tended to be chosen based on the easiness of cultivation and aesthetic aspects. The popular species is janti (Sesbania sesban), which can be called as an alien species because of the lacks of records and information about its existence. The alien species spreading freely and uncontrolled could be potentially invasive. To prove it, an assessment needed to be held. One of procedure that can be used is assessment protocol issued by the nature serve organization, which determines the presence of an invasive type or species based on I-rank, which consists of four assessment categories, namely ecological impact, distribution status and abundance, distribution trends and abundance, and management difficulties. The research result showed that the presence status of Janti was invasive in the middle rank.